ANALISIS EFEKTIVITAS KUALITAS LAYANAN PADA BISNIS KONSULTAN (STUDI KASUS PT KELOLA AMANAH ARTHA) - Rizal Akda Pamungkas; Riyan Hadithya S.E.,M.M (Universitas Sarjanawiyata Tamansiswa, 2024)
Success is no longer solely determined by the product produced and offered, but by the quality of service provided. High-quality service has become a fundamental aspect that businesses must consider and deliver to customers meet expectations and create satisfaction. Therefor, Service quality is crucial because it directly impacts customer satisfaction, which can be readily shared. Satisfied customers will provide positive reviews and promote company by recommending its services to others. Researcher using qualitative descriptive method, collecting data through interviews to assess how effective the service quality provided by PT Kelola Amanah Artha is for its customers. Based on the results of the analysis, it can be concluded that only the assurance dimension can be said to need improvement because this dimension is dominated by customer responses which feel inadequate.